Autohesion and cohesion durability of combined polymeric coverages on arboreal linings - Savenets , Mykola (Forestry, Forest, Paper and Woodworking Industry, 2024)
The given is generalized method of determination of autohesion and cohesion durability of polymeric coverages, experimental information is analysed in an aggregate with theoretical bases of problem.